Characterization Of E. Coli Isolates Of Buffalo Meat Origin For Papc Virulence Gene - Kunal, K.K.; Chhabra, Daljeet; Barbuddhe, S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Twenty nine E. coli isolates belonging to 12 serotypes and rough strains recovered from buffalo meat were characterized for papC gene. The PCR assay was standardized and the primer set for this gene allowed amplification of 501bp. Amplified product of the gene viz. papC was revealed in 23 (79.3%) E. coli isolates belonging to 12 serogroups O12, O24, O35, O60, O69, O88, O114, O139, O159, O168, O169, O172 and rough strain.